Same species, different diseases: how and why typhoidal and non-typhoidal Salmonella enterica serovars differ - Gal-Mor, Ohad; Boyle, Erin C.; Grassl, Guntram A. (Frontiers in Microbiology, 2014)
Human infections by the bacterial pathogen Salmonella enterica represent major disease burdens worldwide. This highly ubiquitous species consists of more than 2600 different serovars that can be divided into typhoidal and non-typhoidal Salmonella (NTS) serovars. Despite their genetic similarity, these two groups elicit very different diseases and distinct immune responses in humans. Comparative analyses of the genomes of multiple Salmonella serovars have begun to explain the basis of the variation in disease manifestations. Recent advances in modeling both enteric fever and intestinal gastroenteritis in mice will facilitate investigation into both the bacterial- and host-mediated mechanisms involved in salmonelloses. Understanding the genetic and molecular mechanisms responsible for differences in disease outcome will augment our understanding of Salmonella pathogenesis, host immunity, and the molecular basis of host specificity. This review outlines the differences in epidemiology, clinical manifestations, and the human immune response to typhoidal and NTS infections and summarizes the current thinking on why these differences might exist.